Meningkatkan Minat Baca Siswa melalui Program Reading Classroom di SDN 2 Mamben Daya - Rizal, Syamsur (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
Comparatively speaking to other nations, Indonesian society has a low level of interest in reading.The absence of a reading habit is the main cause of this low level of interest in reading.The Reading Classroom Program is one way to foster reading habits at a young age, which is necessary to address this issue.The goal of the Reading Classroom Program is to improve elementary school pupils' reading comprehension and interest.This program consists of a number of elements, such as introducing books, generating learning activities with the classroom's existing reading materials, and coming up with reading exercises that encourage students' creativity.By implementing the Reading Classroom Program, this Classroom Action Research (CAR) seeks to increase the reading interest of the students at SDN 2 Mamben Daya.At SDN 2 Mamben Daya, 15 fifthgrade students served as subjects for the two cycles of the study.Observation and interviews were used as data gathering methods, and a descriptive quantitative approach was used for analysis.An increase in students' average reading interest as evaluated by observations and interviews done during each cycle until the predefined goals were met served as the study's success indicator.The study's findings showed that SDN 2 Mamben Daya pupils' enthusiasm in reading had improved.The average observation result in the original condition prior to the intervention was 20.62%. In first cycle, this rose to 69.19%, and in second cycle, it reached 87.71%. From 15.23% in the initial condition to 55.98% in first cycle and 87.19% in second cycle, the average interview results demonstrated an increase.The adoption of the Reading Classroom Program successfully raised the reading interest of pupils at SDN 2 Mamben Daya, according to the research findings.